Application of the Nettest Network Testing Software Package on the Lessons Information Technology - Z. Z. Ibragimov (Peerian Journals Publishing, 2022)
This article presents a feature of the modern system of professional education..
Keywords: Systematic review; satisfactory; client program; server program